The Influence of Brand Image and Experiential Marketing on Consumer Loyalty with Consumer Satisfaction as an Intervening - Maghfur, Rafly fata; Santosa, Perdana Wahyu; Zhafiraah, Nazma Riska (SAN Scientific, 2023)
This study aims to determine whether there is an influence of brand image and experiential marketing on consumer loyalty with consumer satisfaction as mediation in Kopi Kenangan products. The population of this study is Generation Z, aged 12-28 years, who live in Jabodetabek. The sample in this study were people who had bought Kopi Kenangan products at least 2 times within 3 months with a total of 100 respondents. The sampling technique uses a non-probability method with a purposive sampling technique through distributing questionnaires. The analysis method used is the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results showed that Brand Image affects customer satisfaction. Experiential. The managerial implications of the influence of Brand Image and Experiential marketing on consumer loyalty with consumer satisfaction as an intervening variable in Kopi Kenangan in Jabodetabek by Generation Z can include several important aspects, namely strengthening Brand Image by developing brand identity and consistent brand communications as for the implementation of Experiential marketing such as developing memorable experience and quick resolution of complaints.